2014
DOI: 10.5539/esr.v4n1p40
|View full text |Cite
|
Sign up to set email alerts
|

Spacetime: A Distinct Medium

Abstract: String experimentation has allowed for the observation in the laboratory of a D-brane with an open string for visible light (Tahan 2011). Events in experiments when the best defined, largest D-brane appeared suggested the subsistence of a separate medium that was concluded to be spacetime since no other extra-dimensional environment in which light travels could be imagined. Specifically, a high gravitational area in the tube of the set-up rotating and consequently dragging the background in which the light exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…2; D-brane was a surprise. By that, though the pushing influence was known and concluded likely to involve the graviphoton, the influence on spacetime thereby allowing for the observation of the D-brane with the open string was unimagined and particularly due to the largeness of the structure led to the understanding of spacetime to be a distinct medium to which properties can be transferred (Tahan 2015). Conclusions regarding branes were unanticipated when envisioning the possibility of an experiment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2; D-brane was a surprise. By that, though the pushing influence was known and concluded likely to involve the graviphoton, the influence on spacetime thereby allowing for the observation of the D-brane with the open string was unimagined and particularly due to the largeness of the structure led to the understanding of spacetime to be a distinct medium to which properties can be transferred (Tahan 2015). Conclusions regarding branes were unanticipated when envisioning the possibility of an experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The release of superparticles and gravitons by the evaporating high gravitational areas, most precisely string black holes, can be considered a reconciling of quantum mechanics and gravity (Aharony, Gubser, Maldacena, Ooguri, & Oz 2000). Apart from having explained that the size of the largest D-brane with an open string was due to evaporation of, radiated energy from, the biggest black hole in trials thereby demonstrating spacetime to be a specific medium and being supportive of AdS/CFT correspondence (Tahan 2015), the string black holes resolve the information paradox. Additionally, the black holes suggested that singularities need not exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations